2013
DOI: 10.1177/0021998313507615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silane functionalization of alumina whiskers on high-density polyethylene composites

Abstract: New polyethylene matrix and alumina whiskers composites have been designed in order to combine the processability of common thermoplastics with improved physical properties. This work analyzes the influence of the composite formulation on the morphological, rheological and thermal properties of the new materials. Concerning rheological properties, a significant increase in viscosity and storage modulus is observed for high alumina whiskers content. Furthermore, the whiskers were functionalized with silane coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Polymer matrix/nanoparticle incompatibility can be minimized by nanoparticle surface functionalization through silanization reactions . Functionalization of the nanoparticles may improve adhesion between two phases of the mixture, since silane‐based compounds have dual functionality, with one end of the molecule exhibiting a polar group and the other end a nonpolar group .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer matrix/nanoparticle incompatibility can be minimized by nanoparticle surface functionalization through silanization reactions . Functionalization of the nanoparticles may improve adhesion between two phases of the mixture, since silane‐based compounds have dual functionality, with one end of the molecule exhibiting a polar group and the other end a nonpolar group .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding dispersion, parameters such as nanoparticle concentration, processing type, and conditions are critical factors in determining the final properties of nanocomposites . Recently research studies discuss about the importance of chemistry modify and the process parameter in nanocomposites properties, and concluded that the choice for processing technique, in especial by melting process, play an important and significant influence in dispersion of nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…In this way, remarkable increase of mechanical properties of polymer can be expected. Potassium titanate [15−17] , silicon nitride [18,19] , alumina [20,21] , silicon carbide [22] and cellulose [12,23] are among the extensively used whiskers in the research of reinforced polyamide. Tjong et al prepared PA6/potassium titanate composites by melt blending in which filler surface was modified with tetrabutyl orthotitanate prior to mixing [16,24] .…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that a good interfacial adhesion allows an efficient stress transfer between matrix and fillers, which is helpful for the composites to absorb more energy and improve its mechanical properties [12] . Thus, surface modification of CSW is important to the preparation of CSW/PVC composite, and there are many methods available for this purpose, such as in situ grafting polymerization [13] and use of surfactant [14] or coupling agent [15] . However, a variety of control conditions need to be considered in the in situ grafting polymerization, such as contents of emulsifiers and initiators, ratio of monomers/whiskers, reaction temperature, reaction time, deoxygenation and feed mode of monomer; as well as in the surface modification using surfactant or coupling agent, such as pH, temperature and stirring rate.…”
Section: Introductionmentioning
confidence: 99%